Dynamic association of serum albumin changes with inflammation, nutritional status and clinical outcomes: a secondary analysis of a large prospective observational cohort study - Yonghao Li; Liru Chen; Xin Yang; Hongyuan Cui; Zijian Li; Wei Chen; Hanping Shi; Mingwei Zhu (European Journal of Medical Research)
Abstract Background Serum albumin (ALB) has traditionally been regarded as a marker of nutritional status. However, recent studies suggest its changes are closely linked to inflammation, metabolic dysregulation, and disease severity, limiting its role as a sole indicator of nutritional status. Yet, clinical practice continues to rely on ALB to monitor nutritional interventions, with a paucity of high-quality evidence on its dynamic associations with clinical outcomes. This study aimed to investigate the comprehensive associations of ALB dynamics with inflammation, nutritional status, and clinical outcomes in hospitalized patients, providing evidence to optimize clinical management. Methods This secondary analysis utilized data from a prospective observational cohort study conducted in 34 tertiary hospitals across China between June and September 2014. A total of 2959 patients hospitalized for 7–30 days with complete data were included. Standardized protocols were used to collect demographics, nutritional indices (Nutritional Risk Screening 2002, Subjective Global Assessment), hematology, biochemistry results, and clinical outcomes (complications, length of stay, costs). Subgroup analyses were performed based on inflammatory status changes, nutritional therapy administration, department type, baseline nutritional status, and advanced age. Receiver operating characteristic curves identified cutoff values for infection-related complications. Correlation analyses and multivariable linear regression models determined independent predictors of ALB changes. Results Among 2959 patients, 1894 (64.0%) experienced a decrease in ALB during hospitalization, which significantly impacted primary outcomes, including prolonged length of stay, increased hospitalization costs, and higher complication rates. Significant ALB decline was also strongly associated with worsened nutritional status, weight loss at discharge, exacerbated gastrointestinal symptoms, functional impairments, and edema (P < 0.001 for all). Compared to binary categorization (increase vs. decrease), the magnitude of ALB change demonstrated a stronger correlation with infection-related complications across all subgroups. Subgroup-specific cutoff values stratified patients into high- and low-risk groups, with significant differences in infection-related complication rates (P < 0.05), aiding early identification and intervention. Independent predictors of ALB decline included advanced age, surgical status, lower baseline handgrip strength and its change during hospitalization, higher baseline ALB and globulin levels, baseline Prognostic Nutritional Index, baseline inflammatory status and its exacerbation, elevated platelet-to-lymphocyte ratio, and intensive care unit admission. Conclusions Dynamic changes in ALB serve as a critical indicator of inflammation–nutrition interplay, with its reduction effectively predicting infection-related complications, clinical outcomes, and nutritional deterioration. This is particularly valuable in older adults, inflammatory-variable, surgical, and non-malnourished patients. The conventional view of ALB as a pure nutritional marker requires revision. Joint monitoring with inflammatory biomarkers and multidisciplinary interventions targeting high-risk populations are recommended.